The effects of a computer malfunction on subsequent task performance. - Zimmerman, Nichole K.; Sambrook, Everett; Gore, Jonathan S. (Behaviour & Information Technology, 2014)
Although previous research has examined the effects of computer malfunctions on employee frustration, to our knowledge no research has explored computer malfunction's effect on subsequent task performance. It was hypothesised that participants who experience a malfunction would perform worse on a subsequent task than those who experience no malfunction. Participants (n = 204) were randomly assigned to experience either a computer malfunction or not during the first task. Participants then completed a subsequent task. The results confirmed that the Malfunction group performed worse than the Control group on both tasks. Implications for workplace performance are discussed.